SOURCE STUDIES ON THE HISTORY OF RUSSIAN-AFGHAN RELATIONS (BASED ON MATERIALS FROM THE TURKESTAN GOVERNORATE GENERAL) - Ergashev Bakhtiyar Ergashevich (Scholar Express Journals, 2024)
As a result of international relations that developed in the second half of the 19th century, the Russian Empire began an active phase of its activities to colonize Central Asia. As a result, the tactics of relations with the countries of Central Asia were changed. Strong diplomatic ties and planned military operations contradict the interests of two countries in the region: Great Britain and Russia. This article analyzes source studies on the history of RussianAfghan relations based on materials from the Chancellery of the GovernorGeneral of Turkestan.
Keywords: Turkestan; governorship; diplomatic affairs; relations